Ancient worlds in film and television : gender and politics - Renger, Almut-Barbara; Solomon, Jon, 1950- (Metaforms., 2012)
This volume reinvigorates the field of Classical Reception by investigating present-day culture, society, and politics, particularly gender, gender roles, and filmic constructions of masculinity and femininity which shape and are shaped by interacting economic, political, and ideological practices.